[tex] {x}^{y - 3} + x = 2019[/tex]
[tex]x( {x }^{y - 4} + 1) = 2019[/tex]
2019= 1•2019=3•673
Cazuri:
1) x= 2019
[tex]2019( {2019}^{y - 4} + 1) = 2019[/tex]
[tex] {2019}^{y - 4} + 1 = 1[/tex]
[tex] {2019}^{y - 4} = 0[/tex]
=> y-4=0
y=0+4
y=4
2) x=1
[tex]1( {1}^{y -4 } + 1) = 2019[/tex]
=> 1≠2019
3) x=673
[tex]673( {673}^{y - 4} + 1) = 2019[/tex]
[tex] {673}^{y - 4} + 1 = 3[/tex]
[tex] {673}^{y - 4} = 2[/tex]
=> y≠2
4)x=3
[tex]3( {3}^{y - 4} + 1) = 2019[/tex]
[tex] {3}^{y - 4} + 1 = 673[/tex]
[tex] {3}^{y - 4} = 672[/tex]
=> y nu aparține lui N
Răspuns : x=2019 și y=4